Lymph node dissection improved survival in patients with metastatic thoracic esophageal cancer: An analysis of 220 patients from the SEER database. (November 2016) - Wu, San-Gang; He, Zhen-Yu; Wang, Yan; Sun, Jia-Yuan; Lin, Huan-Xin; Su, Guo-Qiang; Li, Qun
Abstract: Background: To assess the clinical value of lymph node dissection and lymph node status in patients with metastatic thoracic esophageal cancer (MTEC). Methods: The Surveillance Epidemiology and End Results (SEER) database was used to identify patients with MTEC who had undergone esophagectomy from 2004 to 2012. Kaplan–Meier survival analysis and Cox proportional hazard regression were used to identify factors significantly associated with overall survival. Results: A total 220 eligible patients were identified, 162 (73.6%) of which underwent lymph node dissection. The 1-year, 3-year, and 5-year overall survival rates were 55.0%, 17.9%, and 9.2%, respectively; the median survival time was 13 months. Lymph node dissection was an independent prognostic factor of overall survival (hazard ratio: 0.527, 95% confidence interval: 0.377–0.736, p  < 0.001). Patients who had undergone lymph node dissection had better overall survival than those who did not (1-year, 62.8% vs. 33.7%; 3-year, 21.4% vs. 7.9%). In patients who had undergone lymph node dissection, multivariate analysis determined that nodal stage was an independent prognostic factor. However, the extent of lymph node dissection was not associated with overall survival. Conclusions: Lymph node dissection improves survival in patients with MTEC who undergo esophagectomy, and the current lymph node staging can be used as a prognostic factor in patients with MTEC. Highlights: Lymph node dissection in metastatic thoracic esophageal cancer is still controversial. Lymph node dissection improves survival in metastatic thoracic esophageal cancer after esophagectomy. The extent of lymph node dissection was not associated with survival in metastatic thoracic esophageal cancer. The lymph node staging can be used as a prognostic factor in metastatic thoracic esophageal cancer.